2019
DOI: 10.18203/2394-6040.ijcmph20191841
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices regarding generic medicines and its usage: a community-based study

Abstract: Background: India is the largest provider of generic medications globally. Despite this, several essential medicines remain inaccessible to majority of the general population, due to poor awareness, unavailability of drugs, distrust about the quality of the medicines, poor policy implementation and inadequate recommendation by doctors.Methods: A community-based cross-sectional study was carried out among 1151 adults in rural and urban areas attached to the community outreach area of a University Medical Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The results obtained about knowledge of generic medicines in our study, are consistent with the results from similar studies carried out in Saudi Arabia, Ethiopia and India. 15,17,39 Our result further showed that the knowledge of community pharmacists was significantly associated with demographic characteristics of the respondents such as gender, age, work experience and country of graduation. This is consistent with the findings of a study carried out in Addis Ababa, Ethiopia.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results obtained about knowledge of generic medicines in our study, are consistent with the results from similar studies carried out in Saudi Arabia, Ethiopia and India. 15,17,39 Our result further showed that the knowledge of community pharmacists was significantly associated with demographic characteristics of the respondents such as gender, age, work experience and country of graduation. This is consistent with the findings of a study carried out in Addis Ababa, Ethiopia.…”
Section: Discussionsupporting
confidence: 59%
“…This concern was equally expressed by some sectors of healthcare workers in a similar study. 39 This may be the reason why community pharmacists 307 (81%) strongly agreed in this study, that there is the need to either educate clients/patients on the medicines that are being administered to them or give adequate information to patients about generic medicines for them to understand better the medication they are taking as indicated in number 9 statement in the perception domain. A high number (90.3%) of the respondents observed that GM will improve access to medicine because they are cheaper than branded products and more affordable.…”
Section: Discussionmentioning
confidence: 82%
“…Generic drug awareness is similar to that obtained in other studies conducted in India. 18,19 In a survey conducted in Brazil, da Rocha et al 20 demonstrated that 95.7% of the respondents had heard about generic drugs. In a National Health Surveillance Agency (ANVISA -Agência Nacional de Vigilância Sanitária) survey, 95% of consumers stated they knew about generic drugs.…”
Section: P-38mentioning
confidence: 99%
“…The Bureau of Pharma PSUs (Public sector undertaking) of India, which operates under the administrative supervision of the Department of Pharmaceuticals, Ministry of Chemicals & Fertilizers, Government of India, is responsible for carrying out the Scheme. (1)The "Jan Aushadhi Scheme" was renamed the "Pradhan Mantri Jan Aushadhi Yojana" in September 2015. To give the program more momentum, it was renamed "Pradhan Mantri Bhartiya Jan Aushadhi Pariyojana" in November 2016.…”
Section: Introductionmentioning
confidence: 99%